Effect of handpiece tip design on the cutting efficiency of an air abrasion system - Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Peruchi, C.; Marker, V. A.; Cordeiro, R. (Mosher & Linder, Inc, 2001)
Purpose : the aim of this study was to evaluate the effect of nozzle angle and tip diameter on the cutting efficiency of an air abrasion system. Materials and Methods: Thirty-six extracted human third molars were air-abraded with the PrepStar microabrasion machine using a handpiece with either 80degrees or 45degrees nozzle angles with 0.38 or 0.48 nun tip orifice diameters. The following parameters were held constant: abrasive particle size (27 mum), air pressure (80 psi), distance (2 mm.) and duration (15 seconds). The cutting efficiency was compared using enamel, dentin and cementum substrates. Width and depth of the cutting patterns were analyzed and measured using scanning electron micrographs. Results: Statistical analysis using three-way ANOVA and Duncan's Multiple Range test revealed that the width of the cuts was significantly greater when the cavities were prepared using the 45degrees nozzle angle. Significantly deeper cavities were produced with the 80degrees nozzle angle. The tip orifice of the nozzle influenced the cutting efficiency in softer substrates, dentin and cementum. Precise removal of hard tissue is best accomplished using the 80degrees angle nozzle tips for all types of tooth surfaces, enamel, dentin and cementum.